An efficient VLSI implementation of lifting based forward discrete wavelet transform processor for JPEG200 - Bhuyan, Mohammad Shaharia; Amin, Nowshad; Madesa, Md. Azrul Hasni; Islam, Md. Shabiul (World Scientific and Engineering Academy and Society (WSEAS), 2007)
This paper describes the hardware design flow of lifting based two-dimensional (2-D) Forward Discrete Wavelet Transform (FDWT) processor for JPEG 2000. In order to build high quality image of JPEG 2000 codec, an effective 2-D FDWT algorithm has been performed on input image file to get the decomposed image coefficients. The Lifting Scheme reduces the number of operations execution steps to almost one-half of those needed with a conventional convolution approach. In addition, the Lifting Scheme is amenable to "in-place" computation, so that the FDWT can be implemented in low memory systems. Initially, the lifting based 2-D FDWT algorithm has been developed using Matlab. The developed codes are then translated into behavioral level of FDWT algorithm in VHDL. The FDWT modules were simulated, synthesized, and optimized using Altera design tools. The final design was verified with VHDL test benches and Matlab image processing tools. Comparison of simulation results between Matlab and VHDL was done to verify the proper functionality of the developed module. The motivation in designing the hardware modules of the FDWT was to reduce its complexity, enhance its performance and to make it suitable development on a reconfigurable FPGA based platform for VLSI implementation. Results of the decomposition for test image validate the design. The entire system runs at 215 MHz clock frequency and reaches a speed performance suitable for several real-time applications.